Exercise Motives and Personal Factors' Effect on Physical Activity of Soccer Players in Albania: A Cross-Sectional Quantitative Study - Bukhari Martinuzzi,; Zamira Madina, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study investigates the potential impact of personal self-efficacy and exercise motives on physical activity levels among soccer players in Albania. The study involved a sample size of 400 participants, utilising the purposive sampling technique. The study employed a cross-sectional research design, adopting a quantitative research approach. The data analysis was conducted using the structural equation modelling (SEM) technique with the assistance of the AMOS software. The findings indicate that the various dimensions of exercise motives have a significant influence on individuals' engagement in physical activity. Interpersonal motives demonstrate a significant and favourable correlation with physical activity, highlighting that individuals driven by social and interpersonal factors are more inclined to participate in physical activity. In contrast, the coefficients of body-related and psychological motives do not exhibit statistical significance in predicting physical activity.On the other hand, there is a notable and positive correlation between fitness motives and personal self-efficacy with physical activity. This suggests that people are more likely to engage in physical activity if they have strong self-confidence and fitness goals. The findings of this study contribute to the comprehension of the motivations and obstacles encountered by soccer players from Albania, thereby offering significant insights for the development of targeted interventions. Practitioners have the opportunity to utilise the inherent allure of soccer, highlighting its positive impact on health and cultivating environments that encourage the adoption of healthier and more physically active lifestyles. Additional investigation is warranted to delve into the intricacies of cultural nuances and demographic adaptations in order to augment the precision and reliability of survey outcomes.